Automated enterprise systems for maximizing business performance - Papajorgji, Petraq (Business Science Reference, 2016)
"This book is a reference source for the latest scholarly research on the modeling and application of automated business systems, featuring extensive coverage on a variety of topics relating to the design, implementation, and current developments of such system"--Resumé vydavatele
Keywords: informační technologie; podnikové informační systémy; automatizace; information technology; management information systems; automation; kolektivní monografie; elektronické knihy; collective monographs; electronic books